Effect of Flipchart-Based Health Education on Knowledge of Pulmonary Tuberculosis Transmission Prevention - Simon Sani Kleden; Irfan; Enggelika Saskia Putri Lengari (Poltekkes Kemenkes Kupang, 2024)
Pulmonary tuberculosis remains a major public health problem in Indonesia, including in the working area of Sikumana Health Center, Kupang City. Lack of family knowledge about the prevention of disease transmission increases the risk of spreading infection within the community. Health education using flipchart media is considered effective in improving public understanding because it is visual, interactive, and easy to comprehend. This study aimed to determine the effect of health education using flipchart media on knowledge of pulmonary tuberculosis transmission prevention among families of patients at Sikumana Health Center, Kupang City, in 2024. This research employed a quantitative method with a one-group pretest-posttest design involving 38 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using the Wilcoxon test. The results showed a significant improvement in knowledge after the health education intervention, with a p-value of 0.000 (p < 0.05). Before the intervention, most respondents had a moderate level of knowledge, which increased to a good category after the intervention. It can be concluded that health education using flipchart media is effective in improving family knowledge regarding the prevention of pulmonary tuberculosis transmission. This medium is recommended for continuous use in health promotion activities at community health centers.